PENGGUNAAN MEDIA KOMIK DIGITAL DALAM MENINGKATKAN MINAT MEMBACA TEKS FIKSI PADA MATA PELAJARAN BAHASA INDONESIA KELAS VI DI SD NEGERI BONTOMAERO 1 KABUPATEN GOWA - Dwi Adeliah Ishak; Andi Adam; Haslinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low interest in reading fictional texts among students, which results in a lack of interest and participation in Indonesian language learning. This condition is caused by the use of learning media that are less interesting and less varied, so students tend to feel bored in reading activities. Therefore, innovation is needed in the learning process, one of which is through the use of digital comic media which is expected to increase students' interest in reading. This study aims to determine the effect of the use of digital comic media on the interest in reading fictional texts of sixth-grade students at Bontomaero I Elementary School, Gowa Regency. The type of research used is quantitative research with a one-group pretest-posttest design. The subjects of the study were all 17 sixth-grade students. Data collection techniques were carried out through administering tests before (pretest) and after (posttest) treatment. Data were analyzed using descriptive statistics and inferential statistics through the Shapiro-Wilk normality test and paired sample t-test with the help of the SPSS program. The results showed that the average pretest score was 55.59 and the average posttest score was 82.35, resulting in an increase of 26.76. The results of the hypothesis test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05 so that H₀ was rejected and H₁ was accepted. Thus, it can be concluded that the use of digital comic media has a significant effect in increasing interest in reading fictional texts of grade VI students of SD Negeri Bontomaero I, Gowa Regency.